Aktywność młodzieży w Internecie a relacje z rodzicami. Wskazania dla nauczycieli do pedagogizacji rodziców = Adolescents` activity on the Internet and their relations with parents. Guidelines for teachers responsible for pedagogization of parents - Łukasik, Joanna M.; Solecki, Roman (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article addresses the issue of relations between contemporary adolescents (deeply rooted in the cyber world) and their parents. The aim of the study was to explore and describe relations between adolescents and their parents viewed through the prism of the motives of undertaking online activity. The main research question was: What are the relations between adolescents active on the Internet and their parents? In the study, the authors used the questionnaire method.
Keywords: relacje rodzic-młodzież; motywy aktywności internetowej; profilaktyka; parent-adolescent relations; motives of Internet activity; prevention